Monotonic uplift behavior of anchored pier foundations in soil overlying rock - Sun, Yizhou; Sun, Honglei; Tang, Chong; Cai, Yuanqiang; Pan, Feng (Journal of Zhejiang University. A. Science, 2023)
Rock-embedded foundations with good uplift and bearing capacity are often used in mountains or hilly areas. However, there are soil layers with a certain thickness on the rocks in these mountainous areas, and the utilization of those soil layers is a problem worthy of attention in foundation construction. Considering construction- and cost-related factors, traditional single-form foundations built on such sites often cannot provide sufficient resistance against uplift. Therefore, an anchored pier foundation composed of anchors and belled piers, specifically constructed for such conditions, can be invaluable in practice. This paper introduces an experimental and analytical study to investigate the uplift capacity and the uplift mobilization coefficients (UMCs) of the anchored pier foundation. In this study, three in-situ monotonic pullout tests were carried out to analyze the load–displacement characteristics, axial force distribution, load transfer mechanism, and failure mechanism. A hyperbolic model is used to fit the load–displacement curves and to reveal the asynchrony of the ultimate limit states (ULSs) of the anchor group and the belled pier. Based on the results, the uplift capacity can be calculated by the UMCs and the anchor group and pier uplift capacities. Finally, combined with the estimation of the deformation modulus of the soil and rock, the verification calculation of the uplift capacity and UMC was carried out on the test results from different anchored pier foundations.